Zonificación de las áreas con posibilidad de inundación aplicando técnicas multicriterio en sistema de información geográfica SIG en el cantón Tisaleo - Merchán Cuno, Silvia Mariela (2025)
The research work entitled “Zoning of areas with the possibility of flooding by applying multicriteria techniques in Geographic Information System (GIS) in the canton of Tisaleo” addresses GIS multicriteria analysis to identify flood zones in the canton of Tisaleo. The research aims to establish a method for zoning areas at risk of flooding, using methods to evaluate and contrast different methods of risk assessment. Hydrological, climatic and topographic data collected from the area, and multi-criteria analysis methods to evaluate variables such as rainfall intensity, topography and vulnerability of the population and infrastructure. The data are presented and analyzed using GIS tools to help identify flood-prone areas and identify areas that are more susceptible to flooding...........